Quality of life after simultaneously integrated boost with intensity-modulated versus conventional radiotherapy with sequential boost for adjuvant treatment of breast cancer: 2-year results of the multicenter randomized IMRT-MC2 trial. (October 2021) - Forster, Tobias; Hommertgen, Adriane; Häfner, Matthias Felix; Arians, Nathalie; König, Laila; Harrabi, Semi Ben; Schlampp, Ingmar; Köhler, Clara; Meixner, Eva; Heinrich, Vanessa; Weidner, Nicola; Hüsing, Johannes; et al.
Highlights: Randomized phase III trial with 502 breast cancer patients, evaluating quality of life. Intensity-modulated radiotherapy with simultaneously integrated boost compared to 3D-conformal radiotherapy with sequential boost. After 6 weeks, pain and arm symptoms superior for simultaneously integrated boost. Non-inferior quality of life compared to 3D-conformal radiotherapy with sequential boost. Results support simultaneously integrated boost application to shorten treatment times. Abstract: Background: We recently published 2-year results of the prospective, randomized IMRT-MC2 trial, showing non-inferior local control and cosmesis in breast cancer patients after conventionally fractionated intensity-modulated radiotherapy with simultaneously integrated boost (IMRT-SIB), compared to 3D-conformal radiotherapy with sequential boost (3D-CRT-seqB). Here, we report on 2-year quality of life results. Patients and Methods: 502 patients were enrolled and randomized to IMRT-SIB (50.4 Gy in 1.8 Gy fractions with a 64.4 Gy SIB to the tumor bed) or to 3D-CRT-seqB (50.4 Gy in 1.8 Gy fractions, followed by a sequential boost of 16 Gy in 2 Gy fractions). For quality of life (QoL) assessment, patients completed the QLQ-C30 and QLQ-BR23 questionnaires at baseline, 6 weeks and 2 years after radiotherapy. Results: Significant differences between treatment arms were seen 6 weeks after radiotherapy for pain (22.3 points for IMRT vs. 27.0 points for 3D-CRT-seqB; p = 0.033) and arm symptoms (18.1 points for IMRT vs. 23.6 points for 3D-CRT-seqB; p = 0.013), both favoring IMRT-SIB. Compared to baseline values, both arms showed significant improvement in global score (IMRT: p = 0.009; 3D-CRT: p = 0.001) after 2 years, with slight deterioration on the role (IMRT: p = 0.008; 3-D-CRT: p = 0.001) and social functioning (IMRT: p = 0.013, 3D-CRT: p = 0.001) as well as the future perspectives scale (IMRT: p = 0.003; 3D-CRT: p = 0.0034). Conclusion: This is the first randomized phase III trial demonstrating that IMRT-SIB was associated with slightly superior QoL compared to 3-D-CRT-seqB. These findings further support the clinical implementation of SIB in adjuvant breast cancer treatment.